EVALUATING THE EFFECTIVENESS OF THE VILLAGE FUND PROGRAMME IN DRIVING LOCAL ECONOMIC DEVELOPMENT - Caroline, Caroline (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The Village Fund programme is one of the Indonesian government policies that aims to promote local economic development through independent budget management by village governments. This study evaluates the extent to which the programme has been effective in improving community welfare and economic development at the village level. The results of the evaluation show that Dana Desa has significantly contributed to improvements in infrastructure, local economic empowerment, and access to public services. However, the implementation of the programme still faces a number of challenges, such as a lack of human resource capacity, weak supervision, and potential budget misuse. To ensure the sustainability and effectiveness of the programme, it is necessary to improve governance, increase transparency, strengthen monitoring mechanisms, and actively involve the community in every stage of implementation. Thus, the Village Fund has a great opportunity to become an effective instrument in supporting sustainable economic development and equalising community welfare in rural areas.